The New Politics of Education and the Pursuit of a Diverse Democracy - Joseph Kahne; John Rogers; Alexander Kwako (AERA Open)
The increasingly partisan politics of education make it vital to conceptualize why and to empirically assess how current partisan pressures threaten public schools’ efforts to educate toward a diverse democracy. We examine these dynamics, drawing on a survey of a large and diverse sample of high school principals, weighted to reflect national demographics, conducted in summer 2022. We find that high schools in purple contexts are particularly likely to experience parent and community pushback related to education toward a diverse democracy and that schools in purple and red communities are less likely to provide support for this priority. By mapping this terrain, the study informs our understanding of the new partisan politics of education, priorities for future research, and, ultimately, directions for strategic action on the part of key stakeholders.